Investigating Aspects Affecting Joe Biden's Speech on the Inauguration of the 46th President of The United States: A Political Discourse Analysis - Yunika Triana; Dewi Zulaiha (Universitas Ahmad Dahlan, 2021)
This paper aims to discover the aspects behind the politic historical events of Joe Biden's state speech. The speech, of course, has close relation with some of the historic American events that had just occurred. The research uses political discourse analysis to find the points uttered by the president who was influenced by ideology, status, and various socio-political contexts. At the inauguration on January 21, 2021, President Joe Biden's first national address is interesting to review. He conveyed messages explicitly to American society, but he also conveyed messages implicitly to political opponents. Researchers found some factors why messages spoken by Joe Biden including addressee, contextual situation, the intention of the utterance, speech act, and verbal act. These are the concerns by researchers as to whom the speech was delivered. It is not only aimed at directing the American society; it was also directed at his political rivals.